FAKTOR PENDORONG ORANG TUA DALAM MENDUKUNG MAHASISWA BERPRESTASI FAKULTAS ILMU SOSIAL DAN HUKUM TAHUN 2024 - Noer Fathia Aini; Budiaman; Sujarwo (STKIP Subang, 2026)
This Study was conducted to determine factor of parental roles in supporting high achieving students in the Faculty of Social and Legal Science in 2024. This study aims to determine what the factor of parental roles in supporting high achieving students in the Faculty of Social and Legal Science in 2024. This study uses a descriptive research method with a qualitative approach, and data collection techniques through observation, interviews, documentation, and literature review. The result of the study indicate that forms of parental roles in supporting high-achieving students in the Faculty of Social and Law Sciences in 2024 are realized in six main interconnected forms, namely: 1) Physical needs, 2) Social needs, and 3) Psychological needs. Keywords: The Factor of parents, supporting of parents, high-achiveing students